From Policy to Practice: A Comprehensive Analysis of The Challenges and Opportunities in Implementing Science Education for Sustainable Development in Nigeria - Endurance Isaac; Abraham Ameh Isaac; Victor Ojoarome Omale; Nosakhare Okoro (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2026)
This paper discusses the issues and opportunities in implementing science education for sustainable development (SESD) in Nigeria. It revealed a significant and persistent disconnect between the country's progressive policies and their actual on-the-ground implementation. Although the country’s policy framework is geared towards global requirements, such as the UN Sustainable Development Goals (SDGs), a multifaceted set of challenges is likely to impede its implementation in Nigeria. These consist of chronic underinvestment, with the education budget in 2025 at 7.3%, significantly lower than UNESCO's recommendation of 15–20%. This financial deficit results in a profound lack of modern infrastructure, a shortage of qualified and motivated teachers, and the reliance on outdated, rote-learning pedagogical techniques. Nevertheless, strategic opportunities for transformation were also presented. These approaches involve multi-stakeholder partnerships among the government, NGOs, and communities, the strategic use of technology to overcome resource constraints, and the reform of teacher training and curriculum to be more practical and problem-based. The conclusion is that it is essential to bridge this gap to transform the country nationally, and that this should be a collective effort to inject more funding, restructure the education system, and establish accountability to realize Nigeria’s potential for a sustainable future.